Enhancing Database Transaction Management through Hibernate in Secure Microservices Architectures - Jaya Krishna Modadugu (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper explores improving database transaction management and security in microservices architectures using Hibernate and modern database techniques. The main purpose is to ensure data consistency, optimize performance, and secure inter-service communication in distributed systems. Microservices often face challenges with separate databases, high traffic, and complex data relationships, which can lead to latency, overload, or data breaches. To address this, the study uses a combined method of literature review and practical implementation. Existing research on Hibernate, connection pooling, secure communication protocols, and graph databases is analyzed to identify best practices. A prototype microservices system is developed using Spring Boot and Hibernate for transaction management. Connection pooling with HikariCP is applied to reduce latency and prevent database overload. Security is enforced using TLS encryption, JWT authentication, and role-based access control for inter-service communication. Selected services are migrated to a graph database, such as Neo4j, to evaluate improvements in handling complex relationships. Findings show that Hibernate ensures ACID-compliant transactions, connection pooling improves database performance, and secure communication prevents unauthorized access. Graph databases reduce query complexity and enhance response times in highly interconnected services. Overall, combining these strategies creates a robust, scalable, and fault-tolerant microservices architecture. This study demonstrates that integrating advanced transaction management, security, and graph database techniques provides an efficient framework for reliable, secure, and high-performance operations in modern microservices systems.